Preparation method of low-ablation refractory concrete
By preparing functionalized alumina and zirconium dioxide sol and performing composite and mixing treatment, zirconium dioxide-coated alumina is formed, which solves the problem of degradation of the strength performance of existing low ablation refractory concrete in low temperature environments, and achieves high refractory resistance, low ablation rate and good freezing resistance.
Patent Information
- Application Number
- CN202510032738.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The strength performance of existing low ablation rate refractory concrete has sharply decreased in low temperature environments and has poor freezing resistance, which limits its use range.
By preparing functionalized alumina and zirconium dioxide sol and performing composite and mixing treatment, zirconium dioxide-coated alumina is formed to improve the refractory and freezing resistance of concrete.
The high refractory performance, low ablation rate and good freezing resistance of refractory concrete are achieved, ensuring that good strength can be maintained under low temperature environments.
Smart Images

Figure CN119526573A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to a method for preparing low-ablation refractory concrete. Background Art
[0002] Low-corrosion refractory concrete is a concrete material with low ablation rate and heat resistance. It can maintain high compressive strength and durability at high temperatures and is widely used in buildings, subways, bridges and other structures.
[0003] The components of low-corrosion refractory concrete mainly include cement, coarse and fine aggregates, water, admixtures and additives; among them, cement is the main cementitious material in concrete, which can provide good bonding properties and mechanical strength; coarse and fine aggregates are the main solid components, which can provide mechanical strength and durability; admixtures and additives are mainly used to improve the heat resistance, corrosion resistance, frost resistance and other properties of concrete.
[0004] Chinese invention patent application CN114380580A discloses a corundum-based low-ablation rate heat-resistant concrete and its preparation method and application, specifically disclosing that the components of the heat-resistant concrete include composite corundum, alumina powder and pure calcium aluminate cement, wherein the composite corundum is composed of microporous corundum and titanium corundum; The heat-resistant concrete produced by this patent has good ablation resistance and high compressive strength, but the refractory concrete produced by this patent has poor frost resistance and its strength performance drops sharply in low temperature environment, which limits its scope of use. Summary of the invention
[0005] In view of the technical problems existing in the prior art, the present invention provides a method for preparing low-ablation refractory concrete, which has good fire resistance, good ablation resistance and good frost resistance.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing low-ablation refractory concrete includes the steps of preparing functionalized alumina, preparing zirconium dioxide sol, compounding and mixing; the specific operations are as follows: 1. Preparation of functionalized alumina (1) Vinylation The α-alumina is placed in a nitric acid solution for soaking, the soaking temperature is 53-57°C, the soaking time is 37-43min, and after the soaking is completed, it is washed and dried to obtain acid-leached alumina; the acid-leached alumina is placed in an ethanol solution, and then oleic acid amide propyl betaine is added, and after stirring evenly, vinyl silane coupling agent A173 is added, and the temperature is increased to 70-73°C, and the reaction is stirred for 4.8-5.2h. After the reaction is completed, the temperature is naturally lowered to room temperature, filtered and washed, and dried at 78-82°C for 23-25h to obtain ethylene alumina; The particle size of the α-alumina is 130-150 nm; The mass concentration of the nitric acid solution is 30-34%; The mass ratio of the α-alumina to the nitric acid solution is 8.3-8.7:53-60; The mass ratio of the acid-leached aluminum oxide, the ethanol solution, the oleic acid amide propyl betaine, and the vinyl silane coupling agent A173 is 7.3-7.7:92-96:1.2-1.4:0.8-1.2.
[0007] (2) Amination Put ethylene aluminum oxide in tetrahydrofuran, add 3-mercapto-1-propylamine, heat to 65-69°C at a rate of 0.8-1.2°C / min, stir to react, the reaction time is 23-25h, the stirring speed is 104-115rpm, after the stirring reaction is completed, cool naturally to room temperature, wash, and dry to obtain functionalized aluminum oxide; The mass ratio of the ethylene aluminum oxide, tetrahydrofuran and 3-mercapto-1-propylamine is 5.4-5.8:107-114:5.3-5.5.
[0008] 2. Preparation of Zirconium Dioxide Sol The zirconium n-butoxide solution was added to deionized water, and after being stirred evenly, a nitric acid solution was added, and the addition rate was controlled to be 1.3-1.7 mL / min. After the addition was completed, the solution was stirred, and the stirring rate was controlled to be 535-547 rpm until the solution was clear and transparent. Polyethylene glycol 200 and L-sorbitol were added, and ultrasonic treatment was performed. The ultrasonic time was 8-12 min, the ultrasonic power was 136-143 W, and the ultrasonic frequency was 28-32 kHz. After the ultrasonic treatment, a zirconium dioxide sol was obtained; The mass concentration of the zirconium n-butoxide solution is 82-86%; The mass concentration of the nitric acid solution is 65-68%; The mass volume ratio of the zirconium n-butoxide solution, deionized water, nitric acid solution, polyethylene glycol 200, and 0.8-1.2 g L-sorbitol is 74-80 mL: 1000 mL: 16-20 mL: 1.2-1.4 g: 0.8-1.2 g.
[0009] 3. Compound The functionalized alumina is added to the zirconium dioxide sol, and sodium dodecylbenzene sulfonate is added for stirring, the stirring speed is 114-125 rpm, the stirring temperature is 62-64° C., and the stirring time is 23-25 h. After the stirring is completed, the alumina is filtered and washed, and finally the alumina is freeze-dried at -42 to -37° C. for 18-22 h to obtain zirconium dioxide-coated alumina. The mass volumes of the functionalized alumina, zirconium dioxide gel and sodium dodecylbenzene sulfonate are 10.1-10.5 g: 69-73 mL: 0.8-1.0 g.
[0010] 4. Mixing Mix ceramsite, aluminate cement, fly ash and zirconium dioxide coated alumina, stir evenly, add steel fiber, montmorillonite powder, polycarboxylate water reducer and mixing aid, continue stirring, the stirring time is 3.0-4.0min, the stirring speed is 210-230rpm, and after the stirring is completed, refractory concrete is obtained; The ceramsite has a particle size of 6.0-6.4 mm and a bulk density of 907-914 kg / m 3 ; The particle size of the montmorillonite powder is 180-220nm; The length of the steel fiber is 4.3-4.7 mm and the diameter is 0.5-0.7 mm; The mass ratio of the ceramsite, aluminate cement, fly ash, zirconium dioxide coated alumina, steel fiber, montmorillonite powder, polycarboxylate water reducer and mixing additive is 98-103:34.2-35.3:72-76:25.5-26.0:10.7-10.7:8.3-8.8:1.8-2.2:18-18.4; The mixing auxiliary agent is a mixture of deionized water, polyvinyl pyrrolidone and cocoyl diethanolamine, and the mass ratio of the deionized water, polyvinyl pyrrolidone and cocoyl diethanolamine is 33-37:1.1-1.4:1.3-1.6.
[0011] Compared with the prior art, the present invention has achieved the following beneficial effects: 1. In the present invention, alumina is firstly dispersed and then treated with a vinyl silane coupling agent so that vinyl groups are grafted onto the surface of alumina. In the amination step, a mercapto group is introduced, and 3-mercapto-1-propylamine is grafted onto the surface of alumina through a mercapto-ene click reaction, so that the surface of alumina is rich in amino groups. In the present invention, zirconium dioxide sol is prepared and then an alcohol reagent is introduced so that the zirconium dioxide sol contains more hydroxyl groups. In the step of compounding zirconium dioxide and alumina, the hydroxyl groups of zirconium dioxide and alumina are bonded with alumina in the form of hydrogen bonds, so that zirconium dioxide is uniformly and firmly coated on the surface of alumina, the coating is tight, the fire resistance is improved, the ablation rate is reduced, it is uniformly mixed with other components, the stability is good, the environmental adaptability is good, and it can still maintain good strength after low-temperature freezing.
[0012] 2. The refractory concrete prepared by the method of the present invention has an ablation rate of 0.31-0.34 mm / s.
[0013] 3. The refractory concrete prepared by the method of the present invention has a 7d compressive strength of 56.8-58.2 MPa, a 7d flexural strength of 10.35-10.66 MPa, a 28d compressive strength of 78.5-79.4 MPa, and a 28d flexural strength of 15.62-15.89 MPa.
[0014] 4. The refractory concrete prepared by the method of the present invention was demoulded after curing for 7 days at room temperature, and then cured for 21 days, and then calcined at 600°C for 2 hours, and then calcined at 960°C for 2 hours. After naturally cooling to room temperature, the compressive strength was measured to be 74.6-76.3 MPa, and the 28d flexural strength was 14.68-15.21 MPa.
[0015] 5. The refractory concrete prepared by the method of the present invention was demolded after curing for 7 days at room temperature, and then cured for 21 days. It was then frozen at -28°C for 24 hours, and then frozen at -45°C for 24 hours. The above was one cycle. After 5 cycles, the concrete was naturally cooled to room temperature. The compressive strength was measured to be 73.8-75.6 MPa, and the 28d flexural strength was 14.60-15.05 MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0017] In order to more clearly understand the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described.
[0018] Embodiment 1: like Figure 1 As shown, the present invention provides a method for preparing low-ablation refractory concrete, which comprises the steps of preparing functionalized alumina, preparing zirconium dioxide sol, compounding and mixing.
[0019] 1. Preparation of functionalized alumina (1) Vinylation 8.5g of α-alumina was immersed in 56g of nitric acid solution at a temperature of 55°C for 40min. After immersion, it was washed and dried to obtain acid-leached alumina. 7.5g of acid-leached alumina was immersed in 94g of ethanol solution, and then 1.3g of oleic acid amide propyl betaine was added. After stirring evenly, 1.0g of vinyl silane coupling agent A173 was added, the temperature was raised to 71°C, and the reaction was stirred for 5.0h. After the reaction was completed, the temperature was naturally lowered to room temperature, filtered and washed, and dried at 80°C for 24h to obtain ethylene alumina. The particle size of the α-alumina is 140 nm; The mass concentration of the nitric acid solution is 32%.
[0020] (2) Amination Place 5.6 g of ethylene alumina in 110 g of tetrahydrofuran, add 5.4 g of 3-mercapto-1-propylamine, heat to 67 °C at a rate of 1.0 °C / min, and stir to react for 24 h at a stirring speed of 110 rpm. After the stirring reaction is completed, naturally cool to room temperature, wash, and dry to obtain functionalized alumina.
[0021] 2. Preparation of Zirconium Dioxide Sol 78 mL of zirconium n-butoxide solution was added to 1000 mL of deionized water, and after stirring evenly, 18 mL of nitric acid solution was added, and the addition rate was controlled to be 1.5 mL / min. After the addition was completed, stirring was performed, and the stirring rate was controlled to be 540 rpm until the solution was clear and transparent, 1.3 g of polyethylene glycol 200 and 1.0 g of L-sorbitol were added, and ultrasonic treatment was performed. The ultrasonic time was 10 min, the ultrasonic power was 140 W, and the ultrasonic frequency was 30 kHz. After the ultrasonic treatment, a zirconium dioxide sol was obtained; The mass concentration of the zirconium n-butoxide solution is 84%; The mass concentration of the nitric acid solution is 66%.
[0022] 3. Compound 10.3 g of functionalized alumina was added to 71 mL of zirconium dioxide sol, and 0.9 g of sodium dodecylbenzene sulfonate was added and stirred at a stirring speed of 120 rpm, a stirring temperature of 63 °C, and a stirring time of 24 h. After the stirring, the mixture was filtered and washed, and finally freeze-dried at -40 °C for 20 h to obtain zirconium dioxide-coated alumina.
[0023] 4. Mixing 101g ceramsite, 34.8g aluminate cement, 74g fly ash and 25.7g zirconium dioxide coated alumina were mixed, and 10.5g steel fiber, 8.5g montmorillonite powder, 2.0g polycarboxylate water reducer and 18.2g mixing aid were added after stirring evenly, and stirring was continued for 3.5min at a stirring speed of 220rpm. After the stirring was completed, refractory concrete was obtained; The ceramsite has a particle size of 6.2 mm and a bulk density of 910 kg / m 3 ; The particle size of the montmorillonite powder is 200 nm; The length of the steel fiber is 4.5 mm and the diameter is 0.6 mm; The mixing auxiliary agent is a mixture of deionized water, polyvinyl pyrrolidone and cocoyl diethanolamine, and the mass ratio of the deionized water, polyvinyl pyrrolidone and cocoyl diethanolamine is 35:1.3:1.5.
[0024] Embodiment 2: 1. Preparation of functionalized alumina (1) Vinylation 8.3g of α-alumina was immersed in 53g of nitric acid solution at a temperature of 53°C for 37min. After immersion, it was washed and dried to obtain acid-leached alumina. 7.3g of the acid-leached alumina was immersed in 92g of ethanol solution, and then 1.2g of oleic acid amide propyl betaine was added. After stirring evenly, 0.8g of vinyl silane coupling agent A173 was added. The temperature was raised to 70°C and stirred for reaction for 4.8h. After the reaction was completed, the temperature was naturally lowered to room temperature, filtered and washed, and dried at 78°C for 23h to obtain vinyl alumina. The particle size of the α-alumina is 130 nm; The mass concentration of the nitric acid solution is 30%.
[0025] (2) Amination Place 5.4 g of ethylene alumina in 107 g of tetrahydrofuran, add 5.3 g of 3-mercapto-1-propylamine, heat to 65 °C at a rate of 0.8 °C / min, and stir to react for 23 h at a stirring speed of 104 rpm. After the stirring reaction is completed, naturally cool to room temperature, wash, and dry to obtain functionalized alumina.
[0026] 2. Preparation of Zirconium Dioxide Sol 74 mL of zirconium n-butoxide solution was added to 1000 mL of deionized water, and after stirring evenly, 16 mL of nitric acid solution was added, and the addition rate was controlled to be 1.3 mL / min. After the addition was completed, stirring was performed, and the stirring rate was controlled to be 535 rpm until the solution was clear and transparent. 1.2 g of polyethylene glycol 200 and 0.8 g of L-sorbitol were added, and ultrasonic treatment was performed. The ultrasonic time was 8 min, the ultrasonic power was 136 W, and the ultrasonic frequency was 28 kHz. After the ultrasonic treatment, a zirconium dioxide sol was obtained; The mass concentration of the zirconium n-butoxide solution is 82%; The mass concentration of the nitric acid solution is 65%.
[0027] 3. Compound 10.1 g of functionalized alumina was added to 69 mL of zirconium dioxide sol, and 0.8 g of sodium dodecylbenzene sulfonate was added and stirred at a stirring speed of 114 rpm, a stirring temperature of 62 °C, and a stirring time of 23 h. After the stirring, the mixture was filtered and washed, and finally freeze-dried at -42 °C for 18 h to obtain zirconium dioxide-coated alumina.
[0028] 4. Mixing 98g ceramsite, 34.2g aluminate cement, 72g fly ash and 25.5g zirconium dioxide coated alumina were mixed, and 10.3g steel fiber, 8.3g montmorillonite powder, 1.8g polycarboxylate water reducer and 18.0g mixing aid were added after stirring evenly, and stirring was continued for 3.0min and 210rpm. After stirring, refractory concrete was obtained; The ceramsite has a particle size of 6.0 mm and a bulk density of 907 kg / m 3 ; The particle size of the montmorillonite powder is 180 nm; The steel fiber has a length of 4.3 mm and a diameter of 0.5 mm; The mixing auxiliary agent is a mixture of deionized water, polyvinyl pyrrolidone and cocoyl diethanolamine, and the mass ratio of the deionized water, polyvinyl pyrrolidone and cocoyl diethanolamine is 33:1.1:1.3.
[0029] Embodiment 3: 1. Preparation of functionalized alumina (1) Vinylation 8.7g of α-alumina was immersed in 60g of nitric acid solution at a temperature of 57°C for 43min. After immersion, it was washed and dried to obtain acid-leached alumina. 7.7g of the acid-leached alumina was immersed in 96g of ethanol solution, and then 1.4g of oleic acid amide propyl betaine was added. After stirring evenly, 1.2g of vinyl silane coupling agent A173 was added, the temperature was raised to 73°C, and the reaction was stirred for 5.2h. After the reaction was completed, the temperature was naturally lowered to room temperature, filtered and washed, and dried at 82°C for 25h to obtain ethylene alumina. The particle size of the α-alumina is 150 nm; The mass concentration of the nitric acid solution is 34%.
[0030] (2) Amination Place 5.8 g of ethylene alumina in 114 g of tetrahydrofuran, add 5.5 g of 3-mercapto-1-propylamine, heat to 69 °C at a rate of 1.2 °C / min, and stir to react for 25 h at a stirring speed of 115 rpm. After the stirring reaction is completed, naturally cool to room temperature, wash, and dry to obtain functionalized alumina.
[0031] 2. Preparation of Zirconium Dioxide Sol 80 mL of zirconium n-butoxide solution was added to 1000 mL of deionized water, and after stirring evenly, 20 mL of nitric acid solution was added, and the addition rate was controlled to be 1.7 mL / min. After the addition was completed, stirring was performed, and the stirring rate was controlled to be 547 rpm until the solution was clear and transparent. 1.4 g of polyethylene glycol 200 and 1.2 g of L-sorbitol were added, and ultrasonic treatment was performed. The ultrasonic time was 12 min, the ultrasonic power was 143 W, and the ultrasonic frequency was 32 kHz. After the ultrasonic treatment, a zirconium dioxide sol was obtained; The mass concentration of the zirconium n-butoxide solution is 86%; The mass concentration of the nitric acid solution is 68%.
[0032] 3. Compound 10.5 g of functionalized alumina was added to 73 mL of zirconium dioxide sol, and 1.0 g of sodium dodecylbenzene sulfonate was added and stirred at a stirring speed of 125 rpm, a stirring temperature of 64 °C, and a stirring time of 25 h. After the stirring, the mixture was filtered and washed, and finally freeze-dried at -37 °C for 22 h to obtain zirconium dioxide-coated alumina.
[0033] 4. Mixing 103g ceramsite, 35.3g aluminate cement, 76g fly ash and 26.0g zirconium dioxide coated alumina were mixed, 10.7g steel fiber, 8.8g montmorillonite powder, 2.2g polycarboxylate water reducer and 18.4g mixing aid were added after stirring evenly, and stirring was continued for 4.0min at a stirring speed of 230rpm. After the stirring was completed, refractory concrete was obtained; The ceramsite has a particle size of 6.4 mm and a bulk density of 914 kg / m 3 ; The particle size of the montmorillonite powder is 220 nm; The length of the steel fiber is 4.7 mm and the diameter is 0.7 mm; The mixing auxiliary agent is a mixture of deionized water, polyvinyl pyrrolidone and cocoyl diethanolamine, and the mass ratio of the deionized water, polyvinyl pyrrolidone and cocoyl diethanolamine is 37:1.4:1.6.
[0034] Comparative Example 1: Based on Example 1, the changes are as follows: The step of preparing functionalized alumina is omitted; the step of preparing zirconium dioxide sol is omitted; The compounding step is to mix 10.3g of α-alumina and 10.3g of zirconium dioxide powder, and mix them evenly to obtain zirconium dioxide-coated alumina; The particle size of the α-alumina powder is 140 nm; the particle size of the zirconium dioxide powder is 120 nm; The rest of the operations are the same.
[0035] Comparative Example 2: Based on Example 1, the changes are as follows: (1) The step of preparing the functionalized alumina is to soak 8.5 g of α-alumina in 56 g of nitric acid solution at a soaking temperature of 55° C. for 40 min. After the soaking, washing and drying are performed to obtain acid-leached alumina, i.e., the functionalized alumina. The particle size of the α-alumina is 140 nm; The mass concentration of the nitric acid solution is 32%.
[0036] (2) The step of preparing zirconium dioxide sol is as follows: adding 78 mL of zirconium n-butoxide solution to 1000 mL of deionized water, stirring evenly, adding 18 mL of nitric acid solution, and controlling the addition rate to be 1.5 mL / min. After the addition is completed, stirring is performed, and the stirring rate is controlled to be 540 rpm until the solution becomes clear and transparent, thereby preparing zirconium dioxide sol; The rest of the operations are the same.
[0037] Performance testing: The refractory concretes prepared in Examples 1-3 and Comparative Examples 1-2 were respectively vibrated and molded in a mold of 150×150×150 mm, and then demolded after curing for 7 days at room temperature. The strength performance was tested, and after further curing for 21 days, the samples to be tested were prepared. The samples to be tested were tested for ablation rate, fire resistance, and low temperature resistance. The fire resistance test method is to place the test samples prepared in Examples 1-3 and Comparative Examples 1-2 at 600°C for 2 hours, and then at 960°C for 2 hours, and then test the strength performance again after the temperature is naturally reduced to room temperature. The method for testing the low-temperature resistance is to freeze the samples prepared in Examples 1-3 and Comparative Examples 1-2 at -28°C for 24 hours, and then freeze them at -45°C for 24 hours. The above is one cycle. After 5 cycles, the samples are naturally cooled to room temperature and the strength performance is tested again.
[0038] The test results are as follows: Table 1 Test data of embodiments and comparative examples
[0039] The invention firstly performs a dispersion treatment on alumina, and then uses a vinyl silane coupling agent to treat it, so that vinyl groups are grafted on the surface of the alumina. In the amination step, a mercapto group is introduced, and 3-mercapto-1-propylamine is grafted on the surface of the alumina through a mercapto-ene click reaction, so that the surface of the alumina is rich in amino groups. The invention prepares a zirconium dioxide sol, and then introduces an alcohol reagent, so that the zirconium dioxide sol contains more hydroxyl groups. In the step of compounding zirconium dioxide and alumina, the hydroxyl groups of the zirconium dioxide and the alumina are combined in the form of hydrogen bonds, so that the zirconium dioxide is evenly and firmly coated on the surface of the alumina, the coating is tight, the fire resistance is improved, the ablation rate is reduced, the zirconium dioxide is evenly mixed with other components, the stability is good, the environmental adaptability is good, and the strength can still be maintained after low-temperature freezing.
[0040] Comparative Example 1: α-alumina and zirconium dioxide powders are directly mixed, resulting in strong agglomeration and poor dispersibility. The two cannot be dispersed evenly, resulting in poor homogeneity and strength of the concrete, which in turn leads to poor fire resistance and low temperature resistance, and high ablation rate. In Comparative Example 2, the aluminum oxide was surface treated to increase the roughness of the aluminum oxide surface, and then placed in a zirconium dioxide sol for coating. The bonding strength between the aluminum oxide and the zirconium dioxide was poor, and the coating was uneven and not firm. The concrete obtained had low strength and poor stability.
[0041] Unless otherwise specified, all ratios and percentages described in the present invention are by mass ratios and percentages are by mass percentages.
[0042] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing low-ablation refractory concrete, characterized in that: The preparation method comprises the steps of preparing functionalized alumina, preparing zirconium dioxide sol, compounding and mixing; The preparation of functionalized alumina comprises vinylation and amination steps; The vinylization step comprises: placing α-alumina in a nitric acid solution for soaking, the soaking temperature is 53-57° C., the soaking time is 37-43 min, and after the soaking, washing and drying to obtain acid-leached alumina; placing the acid-leached alumina in an ethanol solution, and then adding oleic acid amide propyl betaine, stirring evenly, adding vinyl silane coupling agent A173, raising the temperature to 70-73° C., stirring and reacting for 4.8-5.2 h, and after the reaction is completed, naturally cooling to room temperature, filtering and washing, and drying at 78-82° C. for 23-25 h to obtain vinylized alumina; The amination step comprises placing ethylene aluminum oxide in tetrahydrofuran, adding 3-mercapto-1-propylamine, heating to 65-69° C. at a rate of 0.8-1.2° C. / min, stirring for a reaction time of 23-25 hours, stirring at a speed of 104-115 rpm, and naturally cooling to room temperature after the stirring reaction, washing, and drying to obtain functionalized aluminum oxide; The step of preparing the zirconium dioxide sol is as follows: adding a zirconium n-butoxide solution to deionized water, stirring evenly, adding a nitric acid solution, controlling the addition rate to be 1.3-1.7 mL / min, stirring after the addition is completed, controlling the stirring rate to be 535-547 rpm, until the solution is clear and transparent, adding polyethylene glycol 200 and L-sorbitol, and performing ultrasonic treatment, wherein the ultrasonic time is 8-12 min, the ultrasonic power is 136-143 W, and the ultrasonic frequency is 28-32 kHz. After the ultrasonic treatment is completed, the zirconium dioxide sol is obtained; The compounding step is to put the functionalized alumina into the zirconium dioxide sol, add sodium dodecylbenzene sulfonate and stir, the stirring speed is 114-125rpm, the stirring temperature is 62-64°C, the stirring time is 23-25h, after the stirring is completed, filter and wash, and finally freeze-dry at -42 to -37°C for 18-22h to obtain zirconium dioxide coated alumina.
2. The method for preparing low-ablation refractory concrete according to claim 1, characterized in that: In the vinylation step, the particle size of the α-alumina is 130-150 nm; The mass concentration of the nitric acid solution is 30-34%; The mass ratio of the α-alumina to the nitric acid solution is 8.3-8.7:53-60.
3. The method for preparing low-ablation refractory concrete according to claim 2, characterized in that: The mass ratio of the acid-leached aluminum oxide, the ethanol solution, the oleic acid amide propyl betaine, and the vinyl silane coupling agent A173 is 7.3-7.7:92-96:1.2-1.4:0.8-1.
2.
4. The method for preparing low-ablation refractory concrete according to claim 1, characterized in that: In the amination step, the mass ratio of ethylene aluminum oxide, tetrahydrofuran, and 3-mercapto-1-propylamine is 5.4-5.8:107-114:5.3-5.
5.
5. The method for preparing low-ablation refractory concrete according to claim 1, characterized in that: In the step of preparing the zirconium dioxide sol, the mass concentration of the zirconium n-butoxide solution is 82-86%; The mass concentration of the nitric acid solution is 65-68%; The mass volume ratio of the zirconium n-butoxide solution, deionized water, nitric acid solution, polyethylene glycol 200, and 0.8-1.2 g L-sorbitol is 74-80 mL: 1000 mL: 16-20 mL: 1.2-1.4 g: 0.8-1.2 g.
6. The method for preparing low-ablation refractory concrete according to claim 1, characterized in that: In the compounding step, the mass volumes of the functionalized alumina, zirconium dioxide gel and sodium dodecylbenzene sulfonate are 10.1-10.5 g: 69-73 mL: 0.8-1.0 g.
7. The method for preparing low-ablation refractory concrete according to claim 1, characterized in that: The mixing step comprises mixing ceramsite, aluminate cement, fly ash and zirconium dioxide coated alumina, stirring evenly, adding steel fiber, montmorillonite powder, polycarboxylic acid water reducer and mixing aid, and continuing stirring for 3.0-4.0 minutes at a stirring speed of 210-230 rpm. After the stirring is completed, refractory concrete is obtained.
8. The method for preparing low-ablation refractory concrete according to claim 7, characterized in that: The ceramsite has a particle size of 6.0-6.4 mm and a bulk density of 907-914 kg / m 3 ; The particle size of the montmorillonite powder is 180-220nm; The steel fiber has a length of 4.3-4.7 mm and a diameter of 0.5-0.7 mm.
9. The method for preparing low-ablation refractory concrete according to claim 7, characterized in that: The mass ratio of the ceramsite, aluminate cement, fly ash, zirconium dioxide coated alumina, steel fiber, montmorillonite powder, polycarboxylic acid water reducer and mixing additive is 98-103:34.2-35.3:72-76:25.5-26.0:10.7-10.7:8.3-8.8:1.8-2.2:18-18.
4.
10. The method for preparing low-ablation refractory concrete according to claim 7, characterized in that: The mixing aid is a mixture of deionized water, polyvinyl pyrrolidone and cocoyl diethanolamine, wherein the mass ratio of the deionized water, polyvinyl pyrrolidone and cocoyl diethanolamine is 33-37: 1.1-1.4:1.3-1.6。
Citation Information
Patent Citations
Corundum heat-resistant concrete with low ablation rate as well as preparation method and application of corundum heat-resistant concrete
CN114380580A
Preparation method of non-hydrosol gel of high-dispersibility nano zirconia
CN102180516A
Thermal-insulation refractory castable
CN104311047A
High-temperature-resistant modification method of zirconium dioxide coated micron-sized carbonyl iron absorbent
CN115121793A
Zirconium dioxide-aluminium oxide composite powder and process for the production thereof
WO2011157494A1